AN ANALYZE THE CULTURAL CONTENT IN AN ENGLISH TEXTBOOK FOR MERDEKA CURRICULUM - Julia Anugerah Putri; Absharini Kardena; Rahma Wahidha (International Journal of Teaching and Learning, 2025)
This study aims to analyze the cultural content in English textbooksbcustomized for English language learning based on the Indonesia Merdeka curriculum which ideally includes a variety of Indonesian traditional and regional cultures in the textbooks. The book chosen is a book for grade 10 high school entitled English Language for SMA/MA/SMK/MAK Class 10B by Yuniarti Dwi Arini. The purpose of this study is to prove and review the ratio of cultural content in the tenth grade English interaction textbook.Through cultural content analysis, it is hoped that this research will be able to improve the quality of culture in other EFL textbooks in Indonesia. Research design for this study is quantitative method, specifically conceptual content analysis. The coding of was based on cultural categories and the exposure of cultural elements from the content in the textbook. The results of this study show that the percentage of cultural concepts in the analyzed objects is 76%, the percentage of practices is 17%, and the percentage of perspectives and people are 5% and 2% respectively. For the category of culture, there is a ratio of 55% in the target culture of the English speaking country, 24% in the source culture derived from Indonesian culture, and English-speaking country, 24% on the source culture derived from Indonesian culture, and 21% on the international target culture which is a culture that is international target culture which is a culture that is not the target culture. as well as source cultures and cultures that come from a nation that does not consider English as its first or second language.